Multi-Level Cervical Disc Degeneration and Vertigo - Ercan, Serdar; Baloglu, Murat (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
Objective While complaints of pain, loss of strength, and numbness radiating to the neck and arm are common in patients due to cervical disc degeneration, vertigo is a rare symptom. The articles previously published on the subject focus on single-level disk degeneration and its correlation with vertigo. However, in the case of multilevel cervical discopathy, its effect on the severity of vertigo and its response to surgical treatment has not been clarified. Therefore, the objective of the present study is to shed light on the topic.Methods Patients with vertigo complaints in whom all known etiological causes of vertigo had been excluded, but with cervical disc degeneration, were included in the study. The scores on the Visual Analog Scale (VAS) and Cervical Vertigo Evaluation Scale (CVES) were analyzed in terms of numbers of discopathy, spine levels, and differences regarding the preoperative and postoperative status.Results A total of 24 patients (14 with single-level and 10 with multi-level disc degeneration) underwent anterior cervical discectomy. The preoperative CVES score was significantly decreased after surgery. Multi-level disc degeneration causes fewer vertigo symptoms than the single-level kind. No significant correlation between the severity of pain and vertigo was observed.Conclusion Multi-level disc degeneration causes fewer vertigo symptoms. These symptoms decreased after anterior cervical discectomy in cases of single-level disk herniation at upper segments. The surgical intervention could be a favorable choice of treatment. However, the mechanism and treatment approach to cervical vertigo is still a controversial issue.
Keywords: vertigo; dizziness; cervical; disc degeneration